2019
DOI: 10.1108/md-08-2018-0933
|View full text |Cite
|
Sign up to set email alerts
|

Institutional incentives and pressures in Chinese manufacturing firms’ innovation

Abstract: Purpose The purpose of this paper is to investigate how Chinese firms’ innovation is related to their perceived incentives and pressures from the transitioning institutional environment. Design/methodology/approach A sample of 166 manufacturing firms located in Guangdong Province (China) is analyzed using binomial and moderated multiple regression models. Findings The results show that institutional incentives are more effective in promoting incremental innovations than radical ones, whereas institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 50 publications
3
28
1
Order By: Relevance
“…In light of the fact that prior literatures fails to explain the relationship between institutional pressures and ambidextrous innovation through perspective of strategic cognition, the study adopts perspective of institutional theory and organizational ambidexterity to construct a research framework of institutional pressure, strategic cognition and ambidextrous innovation to explain how external institutional pressures affect cluster firms’ ambidextrous innovation through the mediating role of strategic cognition. Consistent with previous findings (Tang et al , 2020; dos Santos et al , 2020), we further found that institutional pressure would promote both explorative and exploitative innovations in all three dimensions. Normative pressure plays more prominent role in promoting innovation of cluster firms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In light of the fact that prior literatures fails to explain the relationship between institutional pressures and ambidextrous innovation through perspective of strategic cognition, the study adopts perspective of institutional theory and organizational ambidexterity to construct a research framework of institutional pressure, strategic cognition and ambidextrous innovation to explain how external institutional pressures affect cluster firms’ ambidextrous innovation through the mediating role of strategic cognition. Consistent with previous findings (Tang et al , 2020; dos Santos et al , 2020), we further found that institutional pressure would promote both explorative and exploitative innovations in all three dimensions. Normative pressure plays more prominent role in promoting innovation of cluster firms.…”
Section: Discussionsupporting
confidence: 91%
“…As the key research content on cognitive ambidexterity, we also found that strategic cognition played a partially meditating role between the effect of institutional pressure and ambidextrous innovation. Under the institutional pressure of cluster policies in China, cluster firms have strong motivation to develop new technology and market opportunities under institutional incentive and institutional pressures (Tang et al , 2020); but to be contrast with Tang et al (2020), institutional pressures are more effective in promoting prospectors’ exploitative innovation by improving current products and technology to expand a mature market and restart the product circle. Defenders still lack innovative motivation under various institutional pressures, so they are conservative in ambidextrous innovation.…”
Section: Discussionmentioning
confidence: 99%
“…Governmental officials in China are more concerned about the implementation of national strategies set by the central government which may not necessarily match the market-driven targets of firms (Li et al, 2018). Although conducting R&D activities with higher risks may enhance firms' innovation capabilities and generate novel technological outputs, sponsored firms are less motivated to do so (Tang et al, 2019). Furthermore, due to the information asymmetry between firms and the government, sponsored firms often lack internal disciplines (Jourdan & Kivleniece, 2017).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, direct R&D grants, as an administrative ex-ante subsidy, are considered to stimulate productive insufficiency of R&D activities due to the misalignment of interests and information asymmetry between governments and subsidy recipients (Jourdan & Kivleniece, 2017;Perez-Sebastian, 2015). This issue is exacerbated in transitional economies because of the stronger public intervention (Tang et al, 2019;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These viewpoints redefine roles and relationships across independent entities to accelerate and amplify learning and to reduce risks (Hagel and Brown 2013 ; Fuentelsaz et al 2018 ; Gretchenko et al 2018 ). The institutional innovation perspective also depends on mechanisms for building scalable, long-term trust-based relationships through learning capabilities (Hao and Yunlong 2014 ; Chittoor et al 2015 ; Phornlaphatrachakorn 2019 ) and increasing awareness of environmental pressures (Chu et al 2018 ; Tang et al 2020a ). Consequently, institutional innovation underpins the government, educational, training, and corporate policies that solve complex social problems, particularly through systematic collaborations between government agencies, universities, industries, and users.…”
Section: Introductionmentioning
confidence: 99%